Prevalence of smoking cigarettes and beliefs regarding smoking habits among medical students: a cross-sectional study in Sudan - Jarelnape, Ahmed Abdalla; Ahmed, Waled; Omer, Suaad; Fadlala, Aida; Ali, Zeinab; Hassan, Mohamed; Ahmed, Ragaa; Hakami, Manal; Ali, Mujtaba; Mohammed, Khalid; Sagiron, Elwaleed; Abdalla, Yahya Hussein; et al. (Frontiers in Public Health, 2023)
Background: Smoking is a widespread issue among university students worldwide. Smoking is one of the most dangerous social phenomena and greatly impacts public health. The current study investigated beliefs and attitudes toward smoking in Sudan, among medical students. Methods: A cross-sectional study was conducted among medical students at Al Neelain University, Sudan, from March to June 2022, using a web-based questionnaire. The questionnaire was composed of 8 items on demographic data characteristics, and 13 items to evaluate beliefs and attitudes toward smoking. The data analysis was performed descriptively using the Statistical Package for Social Science version 24. Results: The results showed that 336 students participated in this study, and the smoking prevalence among students was 48.8% (41.1% among males and 7.7% among females). 76.8% reported smoking daily at a rate of 5 to 10 cigarettes per day. Beliefs of students regarding smoking. 86.8% disagree with selling cigarettes at the university. 68.4% of respondents did not approve of smoking on campus. There is a relationship between smokers' habits and age groups 22- 25 years, is the most smoking category among students (P-value = 0.01). Conclusion: The prevalence of smoking cigarettes among medical students is disturbing, especially since they are future doctors. There is a need to include a plan to reduce smoking among students, which can be incorporated into study courses and special programs.